OPTIMALISASI PENGGUNAAN CCTV DALAM UPAYA PENINGKATAN PENGAWASAN TERMINAL KARGO DI BANDAR UDARA KELAS 1 KALIMARAU BERAU - Julio Andrean Morales Hau’Oni; Ariyono Setiawan; Totok Warsito (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Kalimarau Berau Class 1 Airport is one of the UPBU Airports in Indonesia. As a Class 1 UPBU Airport, Kalimarau Berau Airport serves quite a number of flights, both commercial and cargo flights with different routes. The rapid development of cargo has resulted in the level of supervision at the cargo terminal being increasingly concentrated. The study found that the problem of the unavailability of CCTV facilities at the cargo inspector terminal used would facilitate and improve the supervision of the cargo terminal area. The cargo terminal has a large area so that the supervision system provided must be monitored according to the SOP owned by the supervisory officer in the cargo terminal area. The purpose of this study is to find a solution in the form of CCTV procurement at the cargo inspector terminal used to improve surveillance.